Faktor yang Berhubungan dengan Keluhan Nyeri Punggung Bawah (Low Back Pain) pada Penenun di Desa Letneo Selatan Kecamatan Insana Barat Kabupaten Timor Tengah Utara - Merdiana Ones; Mustakim Sahdan; Deviarbi Sakke Tira (Media Kesehatan Masyarakat, 2021)
Abstract Low Back Pain (LBP) is pain in the back area between the lower ribs and lumbosacral (around the coccyx). The exact incidence of LBP in Indonesia varies from 7.6% to 37%. Cases in East Nusa Tenggara (Kupang City) for diseases of the muscle system and connective tissue show a total of 12,756 cases with a percentage of 7.3%, which ranks sixth out of 10 most diseases in Kupang City in 2018. The purpose of this study was to analyze the factors associated with complaints of low back pain in weavers in South Letneo Village, Insana Barat Sub-District, Timor Tengah Utara District in 2020. This study was an analytic observational study with a cross-sectional design. The sample used in this study consisted of 42 people. Data were analyzed using chi-square with a significance level of α = 0.05. The results showed that of the four research variables studied, all of them had a relationship with complaints of low back pain. The p-value for each variable as follows: age (0,000); working period (0.001); length of work (0,000) and work posture (0.002). Weavers need to have correct work posture and do stretching to minimize the risk of LBP.